Design and Experiment on Single-Chip Microprocessor for MRD Coupling Sensing and Control - Ying-Qing Guo; Tao Liu; Zhao-Dong Xu; Yong Chen (International Journal of Distributed Sensor Networks)
Magnetorheological (MR) damper, a kind of intelligent vibration mitigation device, can be used to reduce the vibration or dynamic responses of structures. Its damping forces can be adjusted in real-time by updating control currents of the MR damper according to the state parameters of the structure. In this paper, a single-chip microprocessor (SCM) for MR damper coupling sensing and control is developed. The SCM has three main functions: the first one is that it can collect the acceleration responses of the structure by using the acceleration sensor in real-time; the second one is that it can use the segmented control strategy to decide the control currents of the MR damper according to the collected acceleration information; the third one is that based on the PWM technology it can realize to accurately supply power for the MR damper. The developed SCM is tested through experiment. The analysis results of the simulation and experiment show that the SCM can collect the state information of the structure in real-time and realize to choose the currents of MR damper accurately to control the damping forces of the MR damper.